Economic and feasibility comparison of the dRIT and DFA for decentralized rabies diagnosis in resource-limited settings: The use of Nigerian dog meat markets as a case study. - Eze U Ukamaka; Andre Coetzer; Terence P Scott; Boniface M Anene; Romanus C Ezeokonkwo; Chika I Nwosuh; Louis H Nel; Claude T Sabeta (Public Library of Science (PLoS), 2020)
BACKGROUND:Rabies lyssavirus (RABV) is the aetiologic agent of rabies, a disease that is severely underreported in Nigeria as well as elsewhere in Africa and Asia. Despite the role that rabies diagnosis plays towards elucidating the true burden of the disease, Nigeria-a country of 180 million inhabitants-has a limited number of diagnostic facilities. In this study, we sought to investigate two of the World Organization for Animal Health (OIE)-recommended diagnostic assays for rabies-viz; the direct fluorescent antibody test (DFA) and the direct rapid immunohistochemical test (dRIT) in terms of their relative suitability in resource-limited settings. Our primary considerations were (1) the financial feasibility for implementation and (2) the diagnostic efficacy. As a case study, we used suspect rabies samples from dog meat markets in Nigeria. METHODS/PRINCIPAL FINDINGS:By developing a simple simulation framework, we suggested that the assay with the lowest cost to implement and routinely use was the dRIT assay. The costs associated with the dRIT were lower in all simulated scenarios, irrespective of the number of samples tested per year. In addition to the cost analysis, the diagnostic efficacies of the two assays were evaluated. To do this, a cohort of DFA-positive and -negative samples collected from dog meat markets in Nigeria were initially diagnosed using the DFA in Nigeria and subsequently sent to South Africa for diagnostic confirmation. In South Africa, all the specimens were re-tested with the DFA, the dRIT and a quantitative real-time polymerase chain reaction (qRT-PCR). In our investigation, discrepancies were observed between the three diagnostic assays; with the incongruent results being resolved by means of confirmatory testing using the heminested reverse transcription polymerase reaction and sequencing to confirm that they were not contamination. CONCLUSIONS/SIGNIFICANCE:The data obtained from this study suggested that the dRIT was not only an effective diagnostic assay that could be used to routinely diagnose rabies, but that the assay was also the most cost-effective option among all of the OIE recommended methods. In addition, the results of our investigation confirmed that some of the dogs slaughtered in dog markets were rabies-positive and that the markets posed a potential public health threat. Lastly, our data showed that the DFA, although regarded as the gold standard test for rabies, has some limitations-particularly at low antigen levels. Based on the results reported here and the current challenges faced in Nigeria, we believe that the dRIT assay would be the most suitable laboratory test for decentralized or confirmatory rabies diagnosis in Nigeria, given its relative speed, accuracy, cost and ease of use.